Peran Ibu Rumah Tangga Dalam Membantu Finansial Kebutuhan Rumah Tangga Melalui Jualan Online - Akbil Mastufatul F; Safira Nuris; Niken Puspitasari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This research discusses the role of housewives in helping the household's financial needs through online sales. In this digital era, selling online has become a side business option that is much sought after by housewives. Selling online can be done anytime and anywhere, therefore housewives can use their free time to sell online. Online sales can also reach a wider market, and online sales can be a source of additional income, income from online sales can be used to meet family needs, such as children's education costs, health costs, or other costs. This research uses a qualitative research method with a phenomenological approach. This approach is one of five approaches in qualitative research and uses liberal feminist theory. The research results show that this can improve family welfare and make housewives more independent and capable family members, thus selling online has become a way for housewives to help family finances, especially in facing economic challenges